THE VULNERABILITY OF THE MIGRANT IN THE AGE OF SMART-BORDERS AND LIE-DETECTING TECHNOLOGIES (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
At the borders, biometric recognition is being used to detect suspicious movements and anticipate the screening of migrants as they enter European borders. To this end, the EU has funded iBorderCtrl, an AI liedetecting system operated by a virtual border guard to interrogate travelers trying to cross borders by assessing facial microexpressions. Facial recognition raises serious concerns, among them the danger of surveillance and discriminatory profiling, which draw the edges of a group vulnerability. In addition, the creation of biometric records within the interoperability dimension contributes to exacerbating the vulnerability of the migrant.
Keywords: Migrants; lie-detecting; biometrics; vulnerability; border control